Heterogeneous conversion of CO2 into cyclic carbonates at ambient pressure catalyzed by ionothermal-derived meso-macroporous hierarchical poly(ionic liquid)s. Issue 12 (7th September 2015) - Wang, Xiaochen; Zhou, Yu; Guo, Zengjing; Chen, Guojian; Li, Jing; Shi, Yuming; Liu, Yangqing; Wang, Jun
Abstract : Meso-macroporous hierarchical poly(ionic liquid)s are ionothermally synthesized through self-polymerization of the new divinylimidazole IL, exhibiting enhanced CO2 capture and excellent activity in the cycloaddition of CO2 to epoxides. Abstract : Meso-macroporous hierarchical poly(ionic liquid)s (MPILs) with extremely high ionic site densities and tunable pore structures were ionothermally synthesized through the free radical self-polymerization of our newly designed rigid bis-vinylimidazolium salt monomer. The synthesis avoided the use of any templates, gave a high yield (>99%) and allowed recycling of the IL solvent; thus it is facile, atom-efficient, environmentally friendly and sustainable. The synthesized MPILs possessed distinctive features of polycation matrices, abundant halogen anions, and large surface areas. They not only presented enhanced CO2 capture, but led to breakthroughs in the heterogeneous catalytic conversion of CO2 into cyclic carbonates: (1) unprecedented high activity at atmospheric pressure and low temperature; (2) good substrate compatibility, even being active towards the extremely inert aliphatic long carbon-chain alkyl epoxides. This result renders the first occasion of a metal–solvent–additive free recyclable heterogeneous cycloaddition of CO2 at such mild conditions.